Electrochemically active, novel layered m-ZnV2O6 nanobelts for highly rechargeable Na-ion energy storage. (1st July 2016) - Sun, Yan; Li, Chun-Sheng; Yang, Qiu-Ran; Chou, Shu-Lei; Liu, Hua-Kun
Graphical abstract: Abstract: Electrode materials with a three-dimensional (3D) layered framework and excellent electrochemical stability can provide a new avenue for enhancing the overall performance of promising sodium ion batteries. Here, we show that layered monoclinic (m ) - ZnV2 O6 nanobelts with high chemical activity for Na-ion energy storage have been effectively fabricated via a rapid microwave irradiation method over the reaction time of 8 h, in which the fabricating efficiency is 24.5 times greater in comparison with the traditional hydrothermal method. The morphology and phase evolutions were verified by means of X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. This study also proposes the "topotactic transformation−Ostwald ripening" mechanism in layered m -ZnV2 O6 nanobelts, from one-dimensional (1D) m -Zn2 V2 O7 with tunnel structure to a 3D m -ZnV2 O6 layered structure. In particular, the m -ZnV2 O6 nanobelt anode exhibited a high discharge capacity of 480.5 mAh g −1 at a current density of 10 mA g −1, and maintained the considerable discharge capacity of 246.9 mAh g −1 at the 100 th cycle. The very preliminary results are promising and confirming that layered metallic vanadium can give a new insight into designing novel anode materials for high-efficiency energy storage in sodium ion batteries.